Should mast cells be considered therapeutic targets in multiple sclerosis? - Pinke, Karen [UNESP]; Zorzella-Pezavento, Sofia [UNESP]; Lara, Vanessa; Sartori, Alexandrina [UNESP] (Wolters Kluwer, 2020)
Mast cells are immune cells of the myeloid lineage that are found throughout the body, including the central nervous system. They perform many functions associated with innate and specific immunity, angiogenesis, and vascular homeostasis. Moreover, they have been implicated in a series of pathologies (e.g., hypersensitivity reactions, tumors, and inflammatory disorders). In this review, we propose that this cell could be a relevant therapeutic target in multiple sclerosis, which is a central nervous system degenerative disease. To support this proposition, we describe the general biological properties of mast cells, their contribution to innate and specific immunity, and the participation of mast cells in the various stages of multiple sclerosis and experimental autoimmune encephalomyelitis development. The final part of this review is dedicated to an overview of the available mast cells immunomodulatory drugs and their activity on multiple sclerosis and experimental autoimmune encephalomyelitis, including our own experience related to the effect of ketotifen fumarate on experimental autoimmune encephalomyelitis evolution.
Keywords: central nervous system; degenerative disease; experimental autoimmune encephalomyelitis; immunity; immunomodulatory drugs; inflammatory disease; ketotifen fumarate; mast cells; multiple sclerosis; therapeutic target